Effects of Changes in Temperature and CO2 Concentration on Maize Yields in the Loess Plateau - Ma, Chenguang; Lei, Na; Zhang, Fang; Shi, Lei; Zhang, Jing; Dai, Yilun (International Journal of Agriculture and Food Sciences Research, 2024)
Addressing the impact of climate change on food security is now one of the most important challenges facing humanity in the twenty-first century. As one of the three major food crops in China, maize is widely planted on the Loess Plateau and is also a major source of local agricultural income. Therefore, accurately assessing the impacts of climate change on local maize production and formulating corresponding adaptive measures are of great theoretical and practical value in reducing the impacts of climate change and guaranteeing the sustainable development of local agriculture. In this study, we calibrated and validated the parameters of the APSIM model using maize field trial data from 2009 to 2012 in Yuzhong County to assess the applicability of the model in the local area. Effect of using measured climate data from 1979 to 2018 and changes in climate data based on measured data and different CO2 concentrations (350 ppm, 450 ppm, 550 ppm, 650 ppm and 750 ppm) on maize yield in the region. The results showed that under the same CO2 concentration gradient, with the increase of temperature, corn yield basically showed a decreasing trend, in which the CO2 concentration at 350 ppm corn yield decreased at the greatest rate, the temperature increased by 5 ℃ compared to the baseline yield decreased by 30%; at the same temperature, with the increase of CO2 concentration, corn yield had a small increase, in the baseline temperature case, CO2 concentration at At 750 ppm, corn yields increased by 9% compared to yields at 350 ppm.